Soils of the Mesters Vig District, Northeast Greenland. 1.: The Arctic Brown and Related Soils. - Ugolini, F. C. (Meddelelser om Grønland, 1966)
Pedological investigations conducted in the Mesters Vig district, Northeast Greenland, during the summers of 1961 and 1964, revealed well-drained soils that had previously been reported in Alaska under the name of Arctic Brown and in Siberia as Arctic Sod. The presence of Arctic Brown soil in Greenland is a link between the North American and Eurasian continents and establishes the Arctic Brown as a circumpolar soil. The areal distribution of the Arctic Brown and other well-drained soils is larger at Mesters Vig, because of well-drained conditions, than for some arctic areas of Alaska. It has been estimated that the Arctic Brown soil at Mesters Vig covers about ten percent of the area. The distribution and the properties of the Arctic Brown soil depend on drainage, texture of the substratum, stability of the site, and time. Physical and chemical data for a typical Arctic Brown indicate an accumulation of fines at the surface, an acid reaction, a concentration of organic matter at the surface, and an even distribution of free iron oxides throughout the profile. Podzol-like and Arctic Brown soils coexist in the district. An idealized latitudinal sequence of the zonal soils of the ice-free areas of Greenland should show from south to north the succession from Podzols to Arctic Brown to Polar Desert soils.